Efforts of the Samapta Tipiring Unit in Preventing Liquor Circulation in the Jurisdiction of the Nganjuk Police (Advances in Police Science Research Journal, 2024)
The population density that occurs in Nganjuk Regency has an impact on community activities, one of which is committing a criminal offense. The Nganjuk Police Tipiring Unit revealed cases of illegal liquor distribution which increased significantly from 170 to 252 cases in 2022. This shows that the Nganjuk Police Tipiring Unit's efforts in handling illegal liquor tipiring units have not been optimal. This research aims to describe and analyze the implementation of the Nganjuk Police Tipiring Unit and the factors that influence the prevention of the distribution of illegal liquor in the jurisdiction of the Nganjuk Police. This study uses research literature that refers to previous research as well as conceptual literature consisting of the concept of effort, the concept of tipiring, the concept of alcohol, management function theory, communication theory and SWOT theory. The methodology used in this research is a case study with a qualitative approach through interviews, observation and document study. Based on the research results, it can be concluded that the implementation of handling illegal liquor bins is not optimal due to the insufficient number of personnel, inadequate infrastructure and lack of information revenue regarding the circulation of liquor. Apart from that, there are factors that influence internally and externally. Researchers suggest taking several important steps to optimize the implementation of handling illegal liquor tipiring by the Nganjuk Police Tipiring Unit.
Keywords: Unit Tipiring, Peredaran, Minuman Keras